2023
DOI: 10.3390/polym15020464
|View full text |Cite
|
Sign up to set email alerts
|

Color Stability of Polymer-Based Composite CAD/CAM Blocks: A Systematic Review

Abstract: Background: This systematic review aims to evaluate the color stability of resin composite CAD/CAM blocks (CCB) when submitted to staining solutions. Methods: A systematic search was performed on different databases (Embase, Medline, Scopus, Web of Science). Search terms were: ‘polymer infiltrated’, ‘polymer-based’, ‘resin nanoceramic’, ‘resin ceramic’, ‘hybrid composite’, ‘hybrid ceramic’, ‘composite ceramic’, ‘resin infiltrated’, ‘CAD-CAM’, ‘CAD/CAM’, ‘color stability’, ‘staining’, ‘staining susceptibility’,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 51 publications
2
34
0
Order By: Relevance
“…The use of CAD/CAM composite blocks, also known as nano-hybrid ceramic, resin nano-ceramic, resin ceramic, nanohybrid restorative materials, resin-based composite blocks, or hybrid composites, has become increasingly popular due to their superior quality compared to conventional composite materials used in conventional analogic dental procedures for both direct and indirect restorations [ 54 ]. This is attributed to the standardized industrial production processes involving high temperature and/or high-pressure polymerization, which facilitate maximum polymer cross-linking and enhance the material’s properties [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…The use of CAD/CAM composite blocks, also known as nano-hybrid ceramic, resin nano-ceramic, resin ceramic, nanohybrid restorative materials, resin-based composite blocks, or hybrid composites, has become increasingly popular due to their superior quality compared to conventional composite materials used in conventional analogic dental procedures for both direct and indirect restorations [ 54 ]. This is attributed to the standardized industrial production processes involving high temperature and/or high-pressure polymerization, which facilitate maximum polymer cross-linking and enhance the material’s properties [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Changes in RBCs’ optical properties depend on the different characteristics of the oral environment, often characterized by abrasive, erosive, and staining challenges [ 2 , 3 ]. Several studies have reported that when resin composites come into contact with staining agents, they absorb extrinsic pigments responsible for color change [ 1 ], irrespective of whether they are intended to be used for direct or indirect restorations [ 4 ]. This effect is also increased when RBCs are exposed to alcoholic and acidic media due to the degradation of the organic matrix [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Data in the literature shows that red wine also has great staining potential due to chromophore particle adhesion onto solid surfaces [ 19 , 20 ]. Deposits might affect surface nanostructure of enamel and dental materials, generating local deposit crusts [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%